Alteration in expression of beta 2 integrins on lamina propria lymphocytes in ulcerative colitis and Crohn's disease - Bernstein, Charles N (Clinical immunology (Orlando, Fla.), 2002)
We have previously demonstrated by immunohistochemistry that mucosal expression of beta 2 integrins was enhanced in Crohn's disease and ulcerative colitis as compared to normal controls. We aimed, therefore, to determine whether there was a corresponding alteration in the expression of CD11a/CD18 (LFA-1), the primary lymphocyte beta 2 integrin, among the principal subsets of lamina propria lymphocytes (LPLs). Accordingly, LPLs were extracted from surgical resection specimens derived from patients with Crohn's colitis, ulcerative colitis, and from noninflamed controls. Following immunofluorescent staining, three-color flow-cytometry analysis identified LPLs on the basis of CD45 side scatter gating, which in turn, were further subdivided into CD4(+), CD8(+), and CD19(+) cells to account for the predominant T and B cells in the lamina propria. Expression patterns of CD11a, the alpha-subunit of LFA-1; CD18, the beta-subunit of LFA-1; and alpha d, a novel alpha-subunit of the beta 2 integrin family were assessed for each of these lymphocyte subsets. In Crohn's disease and ulcerative colitis there was an increased mean percentage expression of CD4(+) cells and CD11a(+) cells compared with noninflamed controls. CD11a was more likely to be expressed on CD4(+) cells in both Crohn's disease and ulcerative colitis and compared with controls and less expressed on CD19(+) cells. It is likely that an influx of CD4(+)11a(+) cells into the lamina propria accounted for these changes. These results suggest that although currently there is great interest in harnessing alpha 4 beta 7 in treatment of inflammatory bowel disease, further consideration should be given to the role of CD11a in these disease states